Stimulus Contrast Information Modulates Sensorimotor Decision Making in Goldfish - Otero Coronel, Santiago; Martorell, Nicolás; Beron de Astrada, Martín; Medan, Violeta (Frontiers in Neural Circuits, 2020)
Animal survival relies on environmental information gathered by their sensory systems. We found that contrast information of a looming stimulus biases the type of defensive behavior that goldfish (Carassius auratus) perform. Low-contrast looms only evoke subtle alarm reactions whose probability is independent of contrast. As looming contrast increases, the probability of eliciting a fast escape maneuver, the C-start response, increases dramatically. Contrast information also modulates the decision of when to escape. Although response latency is known to depend on looming retinal size, we found that contrast acts as an additional parameter influencing this decision. When presenting progressively higher contrast stimuli, animals need shorter periods of stimulus processing to initiate the response. Our results comply with the notion that the decision to escape is a flexible process initiated with stimulus detection and followed by assessment of the perceived risk posed by the stimulus. Highly disruptive behaviors as the C-start are only observed when a multifactorial threshold that includes stimulus contrast is surpassed.